2006
DOI: 10.3171/jns.2006.104.4.558
|View full text |Cite
|
Sign up to set email alerts
|

A functional neuroimaging investigation of deep brain stimulation in patients with obsessive–compulsive disorder

Abstract: Acute DBS at the VC/VS target is associated with activation of the circuitry implicated in OCD. Further studies will be necessary to replicate these findings and to determine the neural effects associated with chronic VC/VS DBS. Moreover, additional data are needed to investigate whether pretreatment imaging profiles can be used to predict a patient's subsequent clinical response to chronic DBS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
126
1
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 237 publications
(140 citation statements)
references
References 37 publications
10
126
1
2
Order By: Relevance
“…These latter regions have been described to be hypermetabolic in depressed states. In patients with obsessive-compulsive disorder, selective monopolar stimulation of essentially the same targetFalbeit with a larger single electrode contactFproduced acute metabolic effects after 10-20 min that are generally consistent with those found in our study after 1 week of stimulation, supporting the hypothesis that cortical-thalamic-striatal-cortical circuitry can be modulated by DBS at this target site (Rauch et al, 2006). The group of Mayberg et al (2005) has demonstrated that improvement of depressive symptomatology in response to different treatment modalities including DBS to it is invariably associated with a metabolic decrease in Brodmann area 25 (Cg25).…”
Section: Discussionsupporting
confidence: 88%
“…These latter regions have been described to be hypermetabolic in depressed states. In patients with obsessive-compulsive disorder, selective monopolar stimulation of essentially the same targetFalbeit with a larger single electrode contactFproduced acute metabolic effects after 10-20 min that are generally consistent with those found in our study after 1 week of stimulation, supporting the hypothesis that cortical-thalamic-striatal-cortical circuitry can be modulated by DBS at this target site (Rauch et al, 2006). The group of Mayberg et al (2005) has demonstrated that improvement of depressive symptomatology in response to different treatment modalities including DBS to it is invariably associated with a metabolic decrease in Brodmann area 25 (Cg25).…”
Section: Discussionsupporting
confidence: 88%
“…An initial study using O15-PET imaging in patients from this series found that acute high-frequency DBS increased perfusion of orbitofrontal cortex, anterior cingulate cortex, striatum, pallidum, and thalamus compared to control conditions. Acute DBS at the VC/VS target thus was associated with activation of circuitry implicated in OCD (Rauch et al, 2006). Another potential use of imaging is response prediction.…”
Section: Limitationsmentioning
confidence: 99%
“…Imaging studies of patients with OCD have revealed dysfunctional activity in the orbitofrontal and anterior cingulate cortex, the striatum and the thalamus. Hyperactivity in the orbitofrontal cortex correlates with the severity of OCD; it increases when OCD symptoms are present and decreases with successful medical or surgical treatment [93,94]. OCD has been called folie du doute, referring to pathological doubt.…”
Section: Obsessive-compulsive Disordermentioning
confidence: 99%